Coach`s knowledge needs according to gender and experience - Mesquita, I.; Resende, R.; Graca, A.; Rosado, A.; Romero, J. (World Congress of Performance Analysis of Sport VIII, 2008)
A possible explanation for gender differences in the importance ascribed to Support Knowledge is, probably, the higher priority male coaches concede to the mastery of new technologies in sport. This should be further analyzed in future research. A major finding of this study is that novice coaches acknowledge their educational needs in domains directly related with the sport and on the knowledge related to sport sciences. They also perceived Management knowledge as more necessary than experienced coaches did. As Vargas- Tonsing (2007) argues, for quality of sport coaching to be improved it is necessary to design continuing coaching education programs around coaches` needs. Therefore, the coach education programs must be put into a larger conceptual framework in order to account for the variability of kkowledge that coaches need